The Enhanced Inhibitory Effect of Estrogen on PD-L1 Expression Following Nrf2 Deficiency in the AOM/DSS Model of Colitis-Associated Cancer - Kang, Changhee; Song, Chin-Hee; Kim, Nayoung; Nam, Ryoung Hee; Choi, Soo In; Yu, Jeong Eun; Nho, Heewon; Choi, Jin A.; Kim, Jin Won; Na, Hee Young; Lee, Ha-Na; Surh, Young-Joon (Frontiers in Oncology, 2021)
Nuclear factor erythroid 2–related factor 2 (Nrf2) plays a dual role in carcinogenesis. We previously reported that Nrf2 deficiency enhances the anti-tumorigenic effect of 17β-estradiol (E2) in an azoxymethane (AOM)/dextran sodium sulfate (DSS) model of colitis-associated cancer (CAC). Herein, we aimed to determine a possible explanation for our recent work and investigated the immune microenvironment represented by programmed death-ligand 1 (PD-L1) expression. One week after the AOM injection, mice were administered DSS in drinking water for seven days; daily E2 injections were intraperitoneally administered during this period. The mice were sacrificed 16 weeks after AOM injection and analyzed for PD-L1 expression in the distal colon tissues using Western blotting and immunohistochemistry (IHC). Based on Western blotting results, PD-L1 expression was reduced in Nrf2 knockout (KO) female and E2-treated male mice when compared with their wild-type counterparts, following AOM/DSS treatment; this supports the association of PD-L1 expression with tumor progression. Additionally, this finding was in good agreement with the IHC results for PD-L1. Furthermore, we observed that PD-L1 is predominantly expressed in stromal cells rather than on epithelial cells in the colon. Western blotting revealed that PD-L1 expression in the colon positively correlates with expressions of inducible nitric oxide synthase (iNOS) (male, P=0.002; female, P<0.001) and cyclooxygenase-2 (COX-2) (male, P<0.001; female, P<0.001). Collectively, our findings indicate that estrogen ameliorates the immune microenvironment represented by PD-L1 expression and enhances its effect in the absence of Nrf2.